ANALISIS KEBUTUHAN TENAGA KERJA KEFARMASIAN BERDASARKAN METODE WISN DI RSU SYIFA MEDINA TAHUN 2024 - Fadilah, Yulis Ramdhan; Gustaman, Rian Arie; Annashr, Nissa Noor (Jurnal Kesehatan Komunitas Indonesia, 2025)
Pharmaceutical installations manage and distribute drugs and health supplies. The success of hospital pharmacy services depends on adequate human resources. Syifa Medina Hospital often faces overwork due to a shortage of pharmaceutical personnel, increasing workload. This study analyzes the need for Pharmaceutical Technical Personnel (TTK) using the Workload Indicators Staffing Need (WISN) method. This qualitative research involves four informants: the Head of Pharmaceutical Installation (key informant), a Pharmaceutical Technical Personnel, a pharmacist assistant (main informants), and the Head of Human Resources (supporting informant). Data collection includes observation, interviews, document review, and WISN calculations. Results show that the available working hours total 141,600 minutes per year. The study finds that Syifa Medina Hospital requires nine TTKs for optimal pharmaceutical services, but currently, only six are available. This indicates a shortage of three personnel, leading to excessive workload. To enhance pharmaceutical services, the hospital should recruit additional TTKs.